Value chain development as public policy: Conceptualization and evidence from the agri-food sector in Bangladesh - Rob Kuijpers (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2019)
Value chain development (VCD) has become a popular policy instrument to help farmers in developing countries access markets. While VCD initiated by the private sector has received much attention in the literature, there is yet little research on public-led VCD. This paper pro-vides a conceptualization of public-led VCD and discusses in what context it can be a relevant policy instrument. As an illustration, the paper then describes the project "SAFAL", which di-rectly intervenes in the aquaculture, horticulture, and dairy sector of South-West Bangladesh. Using a matched difference-in-difference methodology, it is estimated that SAFAL increased farmers' output market participation, food production, and smallholder welfare, and reduced the number of days in which participating households were food insecure.
Keywords: Q12; Q13; O13; O19; O22; 330; value chain development; market access; impact evaluation; aquaculture; small-holder; food security